The Influence of Globalization on the Development of Educational Management - Savkiv, Uliana; Sydor , Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article substantiates the impact of globalization on the system of management of education and identifies the main directions of its impact on education. Management of the educational sphere in modern conditions determines the procedure for the establishment and legalization of educational institutions, formation of decisions in the educational sphere, support of the vital activity of the structure and control over functioning and development of educational institutions. In conditions of the globalized world in management of education the issues related to supporting educational initiatives and innovations, creating conditions for stable functioning and development of educational systems, development and self-realization of participants in the educational process, legal and economic protection of education, forecasting and making optimal decisions. designing optimal models of educational systems come to the forefront. On the basis of the analysis of scientific works of the leading domestic and European researchers, the tasks of management of education in conditions of globalization have been summarized: definition of strategies of educational activities, improvement of methodologies of quality of management of education taking into account current trends in social development, working out of innovative approaches to management of educational services, intensification of European integration processes, introduction of information technologies in the system of management of education, development of mechanisms for regulating educational activities in a market environment, modification of scientific approaches to human resources management in education and modernization of training of specialists in management of education. The main ways for improving modern management in the process of implementation of educational policy in Ukraine have been proposed.